Besarnya Putaran Dan Jarak Celah Pada Mesin Roll Type Horison Crosswill Dalam Proses Pencetakan Lembaran Sheet di PT ABC - Herry Darmadi; Ahmad Suaduon Harahap (JURNAL VOKASI TEKNIK, 2025)
The sheeter machine is classified as a milling machine using six rolls that the more advanced the roll the more advanced the rotating speed and serves to carry out the milling process and reduce the moisture content and formic acid solution to grind the rubber into the final product with the name RSS (ribbed smoked sheet). The events that occur from the grinding process of the rubber sheet on the sheeter machine is the thinning of the sheet due to the compressive process between the upper roll and the lower roll in order to get perfect results in accordance with the product standards of the factory, each roll has a different rotation with a gap distance set on the gears connected to the rotating roll shafts. From the results of the study obtained the conclusion of the magnitude of the roll rotation of the sheeter machine, namely the results obtained roll rotation of 45.46 rpm on roll 1, on the 2nd roll 50.34 rpm, roll 3 53.94 rpm roll 4 57.94 rpm roll 5 69.53 rpm and on the last roll of 72.43 rpm. While the discussion of the magnitude of the gap distance in getting a value of 21 mm on roll 1, 13 mm on roll 2, 6 mm on roll 3, 4 mm on roll 4, 3 mm on roll 5, 2 mm on roll 6 for each roller, the relationship between rotation and gap distance is very influential in the process of making sheet sheet RSS (ribbed smoked sheet) which if the rotation speed is too fast it can cause damage to the sheet and what if the gap distance is too large or too small equally cause damage to the sheet.